Preparation of all-oxide β-Ga2O3/α-MoO3 heterojunction towards self-driven deep ultraviolet photosensor. (28th October 2021) - Cui, Yinhua; Zhang, Shaohui; Shi, Qingshan; Hao, Shengcai; Bian, Ang; Xie, Xiaobao; Liu, Zeng
Abstract: A self-driven all-oxide β -Ga2 O3 / α -MoO3 heterojunction solar-blind ultraviolet (UV) photodetector is introduced in this work. The photodetector shows photo responsivity (R) of 0.59 mA W −1, specific detectivity (D*) of 10 11 Jones and linear dynamic region (LDR) of 162.9 dB at 10 V, and R of 0.26 mA W −1, D* of 4 × 10 10 Jones and LDR of 89.44 dB at −10 V. In addition, it could also operate repeatably and stably at zero bias, illustrating that it is a self-driven photodetector. In one word, the fabricated β -Ga2 O3 / α -MoO3 heterojunction has a potential to work as a self-driven solar-blind UV sensing device.